Impact of relationship marketing on customer retention: a study on selected licensed domestic commercial bank in jaffna district - Ketharan, K. (University of Jaffna, 2016)
Banking industries in Sri Lanka are very competitive, and it is difficult for retail banks to provide unique banking services as required by customers. To overcome this challenge, banks, which can be classified as service firms, can benefit from superior relationship marketing, because customers focus on the service aspect and interaction with the service provider when evaluating a service firm. This study is an attempt to investigate the impact of relationship marketing on customer retention of listed licensed commercial banks in Jaffna district. This research focused on primary data collection method which information drawn from 8 licensed commercial banks on basis of convenience sampling method. This study considered relationship marketing as the independent variable which measured by trust, promise, commitment, communication, rewarding and responsiveness. The customer retention is considered as dependent variable. Two hypotheses were tested using correlation and regression analysis through SPSS software (16.0 version).The results of this study revealed that the relationship marketing has significantly correlated with customer retention. Further some relationship marketing variables like responsiveness and rewarding have significantly (p<0.05) impact on customer retention. Furthermore, the finding of the study can be considered as helpful for some persons or institution. Although this study supports the number of earlier studies, it could not provide the conclusive evidence on some important issues.
Keywords: Customer retention; Commitment; Communication licensed commercial bank; Relationship marketing; Trust